Immigration, family responsibilities and the labor supply of skilled native women - Lídia Farré; Libertad González Luna; Francesc Ortega (Institute for the Study of Labor (IZA), 2009)
This paper investigates the effects of Spain's large recent immigration wave on the labor supply of highly skilled native women. We hypothesize that female immigration led to an increase in the supply of affordable household services, such as housekeeping and child or elderly care. As a result, i) native females with high earnings potential were able to increase their labor supply, and ii) the effects were larger on skilled women whose labor supply was heavily constrained by family responsibilities. Our evidence indicates that over the last decade immigration led to an important expansion in the size of the household services sector and to an increase in the labor supply of women in high-earning occupations (of about 2 hours per week). We also find that immigration allowed skilled native women to return to work sooner after childbirth, to stay in the workforce longer when having elderly dependents in the household, and to postpone retirement. Methodologically, we show that the availability of even limited Registry data makes it feasible to conduct the analysis using quarterly household survey data, as opposed to having to rely on the decennial Census.
urn:nbn:de:101:1-2009080752
Keywords: J61; J22; J13; 330; Immigration; labor supply; fertility; retirement; household services; Einwanderung; Frauenerwerbstätigkeit; Hauspersonal; Weibliche Führungskräfte; Hochqualifizierte Arbeitskräfte; Arbeitsangebot; Familie-Beruf; Altersgrenze; Spanien